PREDICTING FRACTURE FRACTURE FAILURE BASED ON AN ANALYSIS OF RISK FACTORS DETERMINED BY PATIENT CHARACTERISTICS - Kylymniuk, L.O. (The Ukrainian Scientific Medical Youth Journal, 2017)
Relevance. Disorders of osteoreparation become a serious problem of modern traumatology and orthopedics. The high incidence of complications of reparative osteogenesis, period of treatment, incapacity for work causes significant economic costs and the urgency of further study. Aim: to establish the values of risk factors determined by patient characteristics in predicting fracture healing complications. Materials and Methods. The data of 67 patients with fracture healing complications of long tubular bones and 67 patients with analogous fractures without disorders of reparative regeneration, whowere treatedat the Department of traumatology in Vinnytsia Clinical Emergency Hospital, were analyzed. The average age was 49.67 ± 16.32 years. Delayed unionwas established in 25 (37.31%) patients, nonunion in 42 (62.69%). There was no significant difference in gender and age characteristics between patients of both groups. The probability of an error-free forecast was set at pd”0.05. The statistical processing of the data was carried out using the program Statistica 10. Results. Among the lifestyle’s factors a direct relationship with the probability of fracture healing complications was established in the smokers of the study group (р=0.002). Among the comorbid conditions, the highest chances are found in patients with diabetes mellitus (р=0.02), peripheral vascular diseases (р=0.0003), systemic connective tissue diseases (р=0.01), anemia (р=0,004) and hypothyroidism (р=0.02). A significantly higher risk of fracture healing complicationswas found in patients who tooknonsteroidalantiinflammatory drugs from causes not related to trauma (p=0.000005). Acceptance of glucocorticosteroid drugs (p=0.006) and anticoagulants (p=0.009) was also associated with a higher risk of osteoreparation disorders. Conclusion. As a result of the study, it was found that the presence of additional factors increases the risk of fracture healing complications.